Comparative study of legal protection for migrant workers in participation of social security programs in Indonesia and Singapore - Nur Putri Hidayah (Faculty of Law, University of Muhammadiyah Malang, 2020)
Social security is one of the basic rights of workers both local and migrant workers as stated on Art. 25 Universal Declaration of Human Rights. The enactment of single markets and production based in the era of ASEAN Economic Community inevitably brings migrant workers particularly in Indonesia and Singapore. This must be in line with a proper legal instruments to protect migrant workers’ rights in a social security participation. This study aims to compare on how Indonesia and Singapore provide legal protection to migrant workers in the social security participation and what social security programs that can be followed in both countries. The research method used is a normative research method with a statute approach. The result of the study shows that Indonesia has provided protection for migrant workers the same way as local workers as stated on Art. 22 Universal Declaration of Human Rights, whereas Singapore only provides the social security to local workers. Migrant workers get the protection through other ways, namely insurance and bilateral/multilateral agreements. For the social security programs followed by migrant workers, both Indonesia and Singapore do not provide the programs related to what has been regulated on Art. 25 Universal Declaration of Human Rights.